Homestead food production and child anemia in Burkina Faso: The mediating roles of mother’s knowledge and production of micronutrient-rich fruits and vegetables - Kennedy, Andrew; Kadiyala, Suneetha; Daniel, Rihan; Poole, Nigel; Olney, Deanna K. (Wiley, 2017)
There is sparse evidence on how integrated agriculture-nutrition interventions can improve child nutrition. In complex programs it is important to investigate hypothesized pathways to impact, estimating the contributions of potential mediators to the impact on nutrition. We use baseline and endline data from a cluster-randomised controlled trial (cRCT) in rural Burkina Faso evaluating a homestead food production (HFP) programme that previously found an improvement in child hemoglobin (Hb) levels over a 2-year period in the treatment (15 villages) compared to the control (25 villages).